Estudo da aplicação de peles naturais exóticas para a confecção de calçados na indústria brasileira - Ribeiro, Kilder César de Araújo (2004)
This work has got an investigation about the politic, economic, ecologic and technologic influences on application of exotic and natural skins into the shoes Brazilian production. This work was made on a project structure. The search for the theory from one practical activity for the right utilization to produce new shoes, it s an important contribution from this study. Trough analytical tools were mapped the productive cycle of exotic skins, from the creation to industrial uses, which demonstrates the legal ways to the sustainable investment and the opportunities and limitations of this kind of matters. This study has as approach the exposition that the shoes industrial sector investments in new natural matters will make possible to add value for Brazilian products. The results are: there s no direct relation between all environmental factors for the evolution of this sector; the management absence affected differently the Brazilian exotic producers; the political action get better results after private investments; there s a direct ecologic influence into this sector; the success of the technological factor is a result of the agreement of all agents; the industrial application of the exotic leathers mustn t is based on practical deductions and there s many legal ways to invest in new natural leathers with a long time without saturation.